Synergistic enzymatic saccharification and fermentation of agar for biohydrogen production. (October 2017) - Wu, Yi-Rui; Zhang, Mingming; Zhong, Mingqi; Hu, Zhong
Highlights: The optimal condition for biohydrogen production from galactose was developed. Agarase AgaXa and NH852 were employed in the synergetic enzymatic saccharification. The agar hydrolysate was assessed for H2 fermentation by Enterobacter sp. CN1. The platform of the bioconversion of agar biomass into biofuels was established. Abstract: Nowadays, marine biomass is gradually considered as another utilizable material for the sustainable bioenergy development. In the present study, galactose, the main component of agar polysaccharide, was utilized for the biohydrogen production by Enterobacter sp. CN1. The highest hydrogen yield of 303.2 mL/g was obtained in the cultivation media containing 5.87 g/L of galactose, together with initial pH of 7.3 and incubation temperature of 36 °C, after the response surface methodology (RSM) analysis. After the saccharification process by the agarase (AgaXa) and neoagarobiose hydrolase (NH852), the agar hydrolysate obtained was further applied to generate biohydrogen by strain CN1. Under the synergistic enzymatic saccharification and fermentation process, the production of biohydrogen was obtained to be 5047 ± 228 mL/L from 50 g/L of agar, resulting in 3.86-fold higher than the control without enzymatic pretreatment.